POLITENESS STRATEGIES PERFORMED BY LECTURERS IN PROPOSAL SEMINARS IN ENGLISH STUDY PROGRAM FACULTY OF CULTURAL STUDIES AT UNIVERSITAS BRAWIJAYA - PUTRI, ANDITA WULANDARI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: face threatening acts, politeness strategies, lecturer This study is about politeness strategies performed by lecturers in EnglishStudy Program at Universitas Brawijaya. There are two problems to be solved; (1) What are FTA strategies commonly performed by lecturers in proposal seminars in English Study Program Faculty of Cultural Studies at Universitas Brawijaya, (2) What politeness are commonly performed by lecturers in proposal seminars in English Study Program Faculty of Cultural Studies at Universitas Brawijaya.This study is categorized as a case study using qualitative approach since itwas made of a group of individuals consisting of English Study Program lecturers. To get the data, the writer observed proposal seminars activities at Universitas Brawijaya.This study reveals that there were 70 utterances containing FTA strategiesperformed by lecturers of English study program. There were 31 Face Threatening Acts (FTAs) performed in baldly on-record strategy, 21 performed in negative politeness strategy which consists of 20 use hedge expression and 1 be pessimistic strategy, 9 performed in positive politeness strategy which consists of 4 noticing hearer’s interests, 2 seek agreement, 1 be optimistic, 1 congratulating, and 1 asserting speaker’s knowledge of and concern for hearer’s wants, and 9 performed in off record strategy. The subject of this study performed 4 type of FTA strategies based on Brown and Levinson (1987), they were bald-on record strategy, positive politeness strategy, negative politeness strategy, and off record strategy. Most lecturers tend to use bald-on record strategy in which they show and express their opinions and suggestions directly and clearly, so that the hearer, in this case is the students, can get the point easily.The researcher suggests the next researchers to conduct studies by obtainingdata from different contexts and situations, such as in result seminar. Theresearcher also suggests the next researcher to use more theories in analysing the data, especially in analysing how another subject of the study in deifferent ages, relationships, or status can applied politeness in daily life.